2017
DOI: 10.1371/journal.pone.0184487
|View full text |Cite
|
Sign up to set email alerts
|

Label-free quantitative 1H NMR spectroscopy to study low-affinity ligand–protein interactions in solution: A contribution to the mechanism of polyphenol-mediated astringency

Abstract: Nuclear magnetic resonance (NMR) spectroscopy is well-established in assessing the binding affinity between low molecular weight ligands and proteins. However, conventional NMR-based binding assays are often limited to small proteins of high purity and may require elaborate isotopic labeling of one of the potential binding partners. As protein–polyphenol complexation is assumed to be a key event in polyphenol-mediated oral astringency, here we introduce a label-free, ligand-focused 1H NMR titration assay to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…The signal shape as well as the signal width, measured as the full width at half maximum (FWHM), indicated high binding affinity to macromolecular coffee melanoidins (Figure 3). The FWHM of 2,3-diethyl-5-methylpyrazine changed from 2.02 Hz in the aqueous reference to 4.16 Hz in the sample with added melanoidins and therefore led to significant signal broadening of 2.14 Hz and was shifted to higher frequencies by 1.42 Hz, which is supported by literature, where it is reported that compounds exhibiting non-covalent π-π interactions studied by NMR spectroscopy often show line broadening and shift of resonances to higher frequencies [36,37,18]. In comparison, the aroma active compounds 4-hydroxy-2,5-dimethyl-3(2H)-furanone and 2,3-butanedione, representing furanones and diketones are mostly unaffected by the addition of the HMW fraction >10 kDa.…”
Section: Figure 2: Aroma Profiles Of the Aqueous Aroma Recombinate (Blue) And The Aroma Recombinate With Added Melanoidins (Red) In Origimentioning
confidence: 53%
See 2 more Smart Citations
“…The signal shape as well as the signal width, measured as the full width at half maximum (FWHM), indicated high binding affinity to macromolecular coffee melanoidins (Figure 3). The FWHM of 2,3-diethyl-5-methylpyrazine changed from 2.02 Hz in the aqueous reference to 4.16 Hz in the sample with added melanoidins and therefore led to significant signal broadening of 2.14 Hz and was shifted to higher frequencies by 1.42 Hz, which is supported by literature, where it is reported that compounds exhibiting non-covalent π-π interactions studied by NMR spectroscopy often show line broadening and shift of resonances to higher frequencies [36,37,18]. In comparison, the aroma active compounds 4-hydroxy-2,5-dimethyl-3(2H)-furanone and 2,3-butanedione, representing furanones and diketones are mostly unaffected by the addition of the HMW fraction >10 kDa.…”
Section: Figure 2: Aroma Profiles Of the Aqueous Aroma Recombinate (Blue) And The Aroma Recombinate With Added Melanoidins (Red) In Origimentioning
confidence: 53%
“…Interactions such as complex formation by e.g. non-covalent (π-π), dipole-dipole or van der Waals interactions were revealed to be disbanded during liquid chromatography because of the dynamic equilibrium between lightly associated complexation partners [18]. Thus, bound and unbound states of the ligands could not be differentiated, and state of the art GC or UHPLC analysis remains not suitable for observing dynamic non-covalent interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the above‐mentioned biologically active molecules is characterized by its specific physicochemical properties and behavior that change after the formation of the complex with the corresponding interacting partner. Based on these alterations, many different approaches to studying the interactions have been used–equilibrium dialysis , nuclear magnetic resonance , circular dichroism , fluorescence‐based techniques , isothermal titration calorimetry , continuous ultrafiltration , surface plasmon resonance (SPR) , Fourier transform infrared spectroscopy , MS , Raman spectroscopy , molecular modeling , HPLC , and thermophoresis , including CE as well. Besides the substantial instrumental development, the necessity of measured data quality as high as possible is essential requirement of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the above-mentioned biologically active molecules is characterized by its specific physicochemical properties and behavior that change after the formation of the complex with the corresponding interacting partner. Based on these alterations, many different approaches to studying the interactions have been used-equilibrium dialysis [2], nuclear magnetic resonance [3], circular dichroism [4], fluorescence-based techniques [5], isothermal titration…”
mentioning
confidence: 99%